Determinant Factors of Social Cohesion and Inclusion of Street Vendors in Jakarta: Key Factor Surviving During Covid-19 Pandemic - Beti Nurbaiti (Journal of Accounting, Business and Management (JABM), 2021)
This study aims to analyze the determinants of one of the sub-dimensions of social capital, namely social cohesion and inclusion on street vendors (PKL) in DKI Jakarta, most of whom are migrants. The study was conducted using primary data from a survey of the masterplan PKL study in DKI Jakarta in 2021 in 5 municipal areas, namely North Jakarta, West Jakarta, Central Jakarta, South Jakarta, and East Jakarta. The survey was conducted on 1409 street vendors. The method used is quantitative using a questionnaire instrument, which is equipped with in-depth interviews. The results showed that during the pandemic, all street vendors experienced a decrease in turnover, income, and profits and needed to adjust their household expenses to survive. During difficult times, they rely on social capital in the form of social cohesion and inclusion, helping each other in terms of business development, business capital support, transfer of knowledge, and trade skills knowledge. This is supported by the results of the social cohesion and inclusion variable measurement model test that has been carried out.